Evaluasi Website Villas & Homestay Kota Wisata Batu Menggunakan Webqual 4.0 dan Importance - Performance Analysis (IPA) - Ebid Dliya'ul Haq; Retno Indah Rokhmawati; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Villas & Homestay kota wisata Batu is a rental agent for villa and hotel in Batu city which was established in 2014. which also provide guide service to facilitate the tourists to find villa or hotel for vacation, and to ease the process of rental transaction they made website of villahotelbatu.com. From a known problem is that many consumers who use sms or whatsapp rather than the booking feature on the website villahotelbatu.com, so the booking feature is considered useless, for that problem we need a method of analysis that can explore the perceptions of consumers related to existing problems. This research uses webqual 4.0 method and importance performance analysis (IPA). This research uses questionnaire using 23 attributes from webqual 4.0, and for analysis uses IPA method consist of gap analysis, level of conformity analysis and quadrant analysis. The result of evaluation of villahotelbatu.com website has a level of <100% compliance that is equal to 93,78%. It means that visitors are not satisfied with the current performance of the website.